Manipuri Phonology - Potsangbam Madhubala (Potsangbam Bhuban singh Trust Imphal, 2002)
This book helps to know sound system of Manipuri and essential terminology.
Keywords: Manipuri; MANIPURI PHONOLOGY; Linguistics; Manipuri; English